Exploring training factors as incentive tools in safeguarding cultural heritage of Malaysian traditional settlements - Mat Radzuan, Indera Syahrul; Mansir, Dodo; Ahmad, Yahaya (SAGE Publication, 2018)
Training and education has become one of the key aspects in improving incentives programme, thus leading to improved cultural heritage preservation within heritage sites. The study investigated the relationship between the importance of training as a tool on incentivizing cultural heritage in selected traditional settlements in Malaysia. Data were collected through a survey from a total of 63 respondents in both Morten and Chitty Village situated at Melaka Historic City and was analysed using IBM SPSS Statistics 23.0 by means of running an exploratory factor analysis (EFA). The 10 indicator items studied for tangible heritage training have satisfactory factor loadings ranging from 0.59 to 0.77 and distribute across 2 extracted factors having satisfactory cumulative variance of 58.36 per cent. Furthermore, the themes of the distributed indicator items enabled the labelling of the 2 extracted factors to being ‘soft skills’ and ‘hard skills’ for tangible heritage training. Similarly, the 9 indicator items studied for intangible heritage training have satisfactory factor loadings ranging from 0.41 to 0.90 and distribute across 2 extracted factors having a satisfactory cumulative variance of 64.42 per cent. Furthermore, the themes of the distributed indicator items across the 2 extracted factors enabled the labelling of the factors to being ‘intangible arts’ and ‘legislation’ for intangible heritage training. These results found that the ‘explored’ indicator items are fit to be used in further structurally modelling both tangible and intangible heritage training as non-financial incentives in sustainably preserving traditional settlements. The implication of this research is its serving as an information support tool for such intended modelling purpose.